Banks, maturity transformation, and monetary policy - Paul, Pascal (Journal of Financial Intermediation, 2023)
Banks engage in maturity transformation and the term premium compensates them for bearing the associated interest rate risk. Consistent with this view, I show that banks’ net interest margins and term premia have comoved in the United States over the last decades. On monetary policy announcement days, bank equity falls more sharply than nonbank equity following an increase in expected future short-term rates, but also responds more positively if term premia increase. These effects are reflected in bank cash-flows and amplified for banks with a larger maturity mismatch. The results reveal that banks are not immune to interest rate risk.